Silver Nanoparticle-Based Ultrasensitive Chemiluminescent Detection of DNA Hybridization and Single-Nucleotide Polymorphisms - Liu, Cheng-Hui; Li, Zheng-Ping; Du, Bao-An; Duan, Xin-Rui; Wang, Yu-Cong (Analytical chemistry (Washington), 2006)
A new nanoparticle-based chemiluminescent (CL) method has been developed for the ultrasensitive detection of DNA hybridization. The assay relies on a sandwich-type DNA hybridization in which the DNA targets are first hybridized to the captured oligonucleotide probes immobilized on polystyrene microwells and then the silver nanoparticles modified with alkylthiol-capped oligonucleotides are used as probes to monitor the presence of the specific target DNA. After being anchored on the hybrids, silver nanoparticles are dissolved to Ag+ in HNO3 solution and sensitively determined by a coupling CL reaction system (Ag+−Mn2+−K2S2O8−H3PO4−luminol). The combination of the remarkable sensitivity of the CL method with the large number of Ag+ released from each hybrid allows the detection of specific sequence DNA targets at levels as low as 5 fM. The sensitivity increases 6 orders of magnitude greater than that of the gold nanoparticle-based colorimetric method and is comparable to that of surface-enhanced Raman spectroscopy, which is one of the most sensitive detection approaches available to the nanoparticle-based detection for DNA hybridization. Moreover, the perfectly complementary DNA targets and the single-base mismatched DNA strands can be evidently differentiated through controlling the temperature, which indicates that the proposed CL assay offers great promise for single-nucleotide polymorphism analysis.